Malevolent Creativity and Personal Features of Young People in Different Socio-Political Conditions: Relationship and Interaction - Natalya V. Meshkova; Margarita N. Bochkova; Oleg E. Kravtsov (Lomonosov Moscow State University, 2024)
Background. The relevance of the study is associated with the activation of malevolent creativity at the macro level in the form of information wars and isolation of Russia, which create threatening socio-political conditions, against the background of the special military operation in Ukraine. Objectives. Objective of the study was to find out whether there are differences at the micro-level in different socio-political conditions in malevolent creativity as well as to identify its connections with personal characteristics: hostility, the trait of "Agreeableness", and moral identity. The following hypotheses were formulated: 1. The level of antisocial creativity varies in different contexts and will be higher in threatening socio-political conditions and 2. the relationship between such personal characteristics as hostility, Agreeableness, moral identity, and malevolent creativity will be different in different socio-political conditions. Study Participants. The study is a cross-sectional one. The first stage was carried out in 2019 with the participation of 81 young students from one of Moscow universities (mean age 19.2, SD = 1.2). 152 young students of the same Moscow university took part at the second stage in 2023 (mean age 19.1, SD = 1.29). Methods. Participants filled out forms with the questionnaires "NEO-FFI" (a shortened version of the questionnaire "NEO PI-R"), BRAQ-24, moral identity questionnaire, "Behavioral features of antisocial creativity". Results. It is shown that there are differences in variables at the microsystem level in different sociopolitical conditions: MC and hostility are significantly lower, and moral identity and cooperation are significantly higher in the sample of 2023. The predictors of MC in the sample of 2023 were the traits of Agreeableness and hostility. In the sample of 2019, the trait of Agreeableness alone predicted MC. Differences in the strength of the relationship between the variables were revealed: in the sample of 2023, the relationship of hostility with antisocial creativity and the trait of Cooperation was significantly stronger than in the sample of 2019. Conclusions. In threatening socio-political conditions, young people with high hostility and low level on the "Agreeableness" trait fall into the risk group, due to the high probability of the realization of creativity in behavior that harms other people, while realization of MC in behavior may be restrained through actualizing moral identity. In a calm and peaceful period, moral identity and hostility are less relevant for the implementation of MC in harmful behavior, since the development of "Agreeableness" is important in this case.